Regulating sex : the politics of intimacy and identity - Bernstein, Elizabeth, 1968-; Schaffner, Laurie (Perspectives on gender (New York, N.Y.), 2005)
Regulating Sex discusses the various ways that sex and sexuality are regulated by government and society. This collection has an impressive array of contributors writing on compelling topics.